The Analysis of Sea Surface Temperature and Containing Water Chlorophyll-A Distribution Using GEE (Google Earth Engine) Code Technology in Sibolga Waters - Mardame Pangihutan Sinaga; Jono Barita Sianipar; Ady Frenly Simanullang; Herna Febrianty Sianipar; Ewin Handoco S; Goldberd Harmuda Duva Sinaga (Politeknik Negeri Batam, 2023)
Research on SST and chlorophyll-a content using GEE Cloud technology in Sibolga Waters has been carried out since February-December 2019. The analysis was carried out using the MODIS AQUA-L3SMI satellite. The SST results showed that it spread evenly from the coast of Sibolga to the sea, which was 28-33 0C and did not fluctuate, while the content of chlorophyll-a spread evenly, from February-April with a value of 0,1-1 mg/m3 varied, namely from June-August, and fluctuations namely in October-December 2019 with an amount of 0,5-2 mg/m3. SST spreads evenly, varies, and fluctuates around the outskirts of Sibolga coastal waters to the middle of Sibolga Waters, which is unsuitable for demersal fish species. Meanwhile, the chlorophyll-a content spreads evenly, varies, and fluctuates. The high content of chlorophyll-a in all waters and the high SST will make a certain type of fish that can live, namely carnivorous fish species. Image data can be used to map SST distribution patterns and chlorophyll-a content in Sibolga Waters.